ANALYSIS OF FACTORS THAT ARE CONSIDERED BY INVESTORS IN STOCKS INVESTMENT DECISION MAKING IN BATAM CITY - Cuandra, Fendy; Tan, Helen (FEB Universitas Sam Ratulangi Manado, 2021)
Abstract:The purpose of this research is to analyze the factors that investors should consider in stock investment decision making. This research was conducted to assess the interest in investing and consideration when investing which is influenced by representative bias, availability bias, and locus of control. This research was tested using Smart PLS application. Data collection from this study was conducted by distributing questionnaires as many as 353 people in Batam city. Representative bias significantly positively affects investment decision making, availability bias significantly and positively in investment decisions, availability bias moderated locus of control has no effect on investment decision making, and representative bias moderated locus of control has no effect on investment decision making. This research facilitates investors in making investment decisions in Batam city, judging from several factors that influence the decision making helps investors in determining investment and considering every factor that influences Decision making.Â Abstrak: Tujuan dari penelitian ini adalah untuk menganalisa faktor yang harus dipertimbangkan investor dalam pengambilan keputusan investasi Saham. Penelitian ini dilakukan untuk menilai ketertarikan dalam melakukan investasi dan pertimbangan saat berinvestasi yang dipengaruhi oleh representative bias, availability bias, dan locus of control. Penelitian ini di uji dengan menggunakan aplikasi Smart PLS. Pengumpulan data dari penelitian ini dilakukan dengan cara menyebarkan kuesioner sebanyak 353 orang yang berada kota Batam. Representative bias secara signifikan positif mempengaruhi investment desicion making, availability bias secara signifikan dan positif dalam keputusan investasi, availability bias yang dimoderasi locus of control tidak berpengaruh terhadap investment decision making, dan representative bias yang dimoderasi locus of control tidak berpengaruh terhadap investment decision making. Penelitian ini memberi kemudahan investor dalam mengambil keputusan investasi di kota Batam, dilihat dari beberapa faktor yang mempengaruhi pengambilan keputusan ini membantu para investor dalam menentukan investasi dan mempertimbangkan setiap faktor yang mempengaruhi Decision making.